MODERN TECHNOLOGIES IN VISUAL ARTS: INTEGRATION, IMPACT, AND PROSPECTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article explores the integration of modern technologies in the field of visual arts and their impact on artistic practice, production, and perception. As digital media and interactive tools reshape contemporary art forms, this research aims to examine the methodological implications of technological convergence in visual art education and production. Drawing from Scopus-indexed articles and relevant dissertations, the study evaluates both the creative opportunities and conceptual challenges posed by new media. The research highlights how digital tools, artificial intelligence (AI), virtual reality (VR), and augmented reality (AR) redefine artistic processes and offer novel pedagogical models for art education.